2015
DOI: 10.1016/j.kjms.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Percentage of free prostate‐specific antigen (PSA) is a useful method in deciding to perform prostate biopsy with higher core numbers in patients with low PSA cut‐off values

Abstract: The aim of this study was to evaluate the predictive role of percentage of free prostate-specific antigen (%fPSA) cut-points in prostate cancer (PCa) detection in patients with total PSA (tPSA) levels between 2.5 ng/mL and 10.0 ng/mL. In total, 1321 consecutive initial transrectal ultrasound (TRUS)-guided 12-core biopsies performed between 2005 and 2011 were evaluated retrospectively. Benign pathologies, high-grade prostatic intraepithelial neoplasia, and atypical small acinary proliferations were categorized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Moreover, many studies focused their attention on other related parameters, such as free-to-total PSA (F/T) values and prostate-specific antigen density (PSAD), showing higher diagnostic accuracy than that with PSA itself [1113]. Two parameters, PSAD, and F/T are most commonly used to improve the diagnostic accuracy of PSA.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many studies focused their attention on other related parameters, such as free-to-total PSA (F/T) values and prostate-specific antigen density (PSAD), showing higher diagnostic accuracy than that with PSA itself [1113]. Two parameters, PSAD, and F/T are most commonly used to improve the diagnostic accuracy of PSA.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used marker in the diagnosis of prostate cancer is PSA [2]. The upper limit for gray-zone PSA has been determined as 10 ng/ml in numerous studies [6][7][8]15,[17][18]. Some other studies, though few in number, suggest that the upper limit for gray-zone PSA may show ethnic variation and propose that this limit is likely to be higher in countries where PCa is less common, particularly in Far Eastern countries [9,19].…”
Section: Discussionmentioning
confidence: 99%
“…The cancer detection rate per core was calculated in accordance with the International Society of Urological Pathology (ISUP) grading system, which is based on primary and secondary Gleason scores [15]. Clinically significant prostate cancer (sPCa) was considered as biopsy Gleason score ≥3+4 or maximum cancer core length ≥5 mm.…”
Section: Histopathological Examinationmentioning
confidence: 99%
“…[25] Yilmaz et al suggested a cut-off of 10% whereas Pourmand et al arrived at 13%. [26][27] The study conducted by Dalva et al came to a cut-off value of 15%. [28] A study conducted on an Indian population (sample size -101 patients) by Thakur et al determined a cut-off value of 12%.…”
Section: Discussionmentioning
confidence: 99%